THE ROLE OF COURTEOUS SALES PRESENTATIONS IN INCREASING SALESFORCE PERFORMANCE - Rusdianti, Endang; Wardoyo, Paulus; Purwantini, Sri (Integrated Journal of Business and Economics (IJBE), 2021)
AbstractThe purpose of the study to verify the research model, Adding to the variable the ability to make courteous sales presentations so that the results of this study can solve the research gap. This research unit is the Rural Bank, and the respondents are the sales force of the Rural Bank (BPR) in Semarang City with 72 people. This research used a purposive sampling technique. Data processing using SmartPls version 2.0. This study succeeded in proving the role of courteous sales presentations in improving the performance of salesforce. Practical implications -This study provides input on the importance of courteous sales presentation.